Entrepreneurship in the Digital Era: Creating Your Own Online Business. (April 2019) - Finkle, Todd A.; Olsen, Timothy
Two soon-to-be graduates of the University of Washington, Terry Smith and Jack Jones, sought to become entrepreneurs and create their own online business. They had an innovative idea—a mobile app that made it easy for groups to plan a night out. As they researched the idea, they realized they would need help with the technology and business model. With limited time and funds, they had to make several decisions regarding their venture including the application's features and the strongest business model.